Oral health knowledge, attitudes, and practices of people living with mental illness: a mixed-methods systematic review - Alisha Maree Johnson; Amanda Kenny; Lucie Ramjan; Toby Raeburn; Ajesh George (BMC, 2024)
Abstract People living with mental illness experience poorer oral health outcomes compared to the general population, yet little is known about their oral health knowledge, attitudes, and practices. The aim of this mixed-methods systematic review was to synthesise evidence regarding oral health knowledge, attitudes, and practices of people living with mental illness to inform preventative strategies and interventions. Database searches were conducted in PubMed, MEDLINE, PsycINFO, CINAHL, ProQuest, and Scopus with no limitations placed on the year of study. All studies available in the English language, that explored the oral health knowledge, attitudes, and/or practices of people with a mental illness were included. Articles were excluded if they primarily pertained to intellectual disability, behavioural and psychological symptoms of dementia, drug and alcohol or substance use, or eating disorders. A thematic synthesis was undertaken of 36 studies (26 high-moderate quality), resulting in 3 themes and 9 sub-themes. Study participants ranged from n = 7 to n = 1095 and aged between 15-83 years with most having a diagnosis of schizophrenia, schizoaffective, or bipolar affective disorder. People diagnosed with a mental illness were found to have limited oral health knowledge, particularly regarding the effects of psychotropic medication. Various barriers to oral health care were identified, including high dental costs, the negative impact of mental illness, dental fears, lack of priority, and poor communication with dental and health care providers. Study participants often displayed a reduced frequency of tooth brushing and dental visits. The findings highlight the potential for mental health care providers, oral health and dental professionals, mental health consumers, and carers to work together more closely to improve oral health outcomes for people with mental illness. The systematic review protocol is registered with the International Prospective Register of Systematic Reviews (PROSPERO), (registration ID CRD42022352122).